Real-world diffusing capacity simulation data: how well do they fit current European Respiratory Society/American Thoracic Society acceptability criteria?. Issue 2 (6th March 2023) - Haynes, Jeffrey M.; Ruppel, Gregg L.; Kaminsky, David A.
Diffusing capacity of the lungs for carbon monoxide ( D LCO ) is an important pulmonary function test for the diagnosis and management of obstructive, restrictive and pulmonary vascular disease. The 2017 European Respiratory Society (ERS)/American Thoracic Society (ATS) standards for single-breath carbon monoxide uptake in the lungs recommend that a weekly D LCO simulation test be performed with a calibrated 3-L syringe [1]. ERS/ATS D LCO standards recommend acceptability ranges for weekly D LCO simulation testing performed with a 3-L syringe. On some devices, the ERS/ATS limits may exceed or not fit a 3-sd range, in which case, simulation ranges based on 3sd may be appropriate. https://bit.ly/3Z0YoZL